International Financial Statistics, August 2015. (International Financial Statistics; International Financial Statistics ;, 2015)
This August 2015 issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. The report also presents country newly reporting monetary data for Israel using the standardized report forms. IFS is a standard source of statistics on all aspects of international and domestic finance. The IMF publishes calculated effective exchange rates data only for countries that have given their approval. From July 1978 to December 1980, the composition of the basket was changed based on updated data for 1972-1976. The weights of some currencies were also changed. The amount of each of the 16 currencies in the revised basket was such as to ensure that the value of the SDR in terms of any currency on June 30, 1978 was the same in the revised valuation as in the previous valuation.